Ethanol production from the fermentation of sterilized wort by electron beam followed by methane production from its vinasse - Calegari, Rubens Perez (2021)
Microbial contamination present in the ethanol fermentation process negatively affects ethanol efficiency and productivity. Currently, to control bacterial contamination, the sucroernegetic industries carry out the acidic treatment of yeast, however, this causes damage to the fermentation, as it promotes stress to the yeast, allows the presence of bacteria and the replacement of the selected yeast during fermentation. Besides, acid treatment is responsible for high levels of sulfate in vinasse, which, when digested, generates H2S, a toxic compound which interferes negatively in the methanogenesis process. For these reasons, the present work proposes the production of ethanol from wort sterilized by electron beam as a substitute for the acid treatment, and anaerobic digestion of the vinasse from the process. The present study was conducted in three stages. First, tests of wort sterilization by electron beam were performed. Second, the fermentation of the irradiated worts was carried out. Third, the anaerobic digestion (AD) of vinasse and the anaerobic co-digestion (AC) of vinasse with filter cake and sugarcane straw were evaluated. Contingencies did not allow the generation of sufficient vinasse for conducting the third stage; therefore, it was decided to use sulfate-rich vinasse from the industry, and to test its AD and AC with the addition of the trace elements (TE) Fe, Ni, Co, Se, Mo, and Zn, in order to circumvent the problems caused by the high sulfate concentration. In the first stage, only the radiation dose of 80 kGy was able to sterilize the wort, however, 40 kGy was sufficient to inactivate >99.99% of the contaminating microorganisms. In addition, there was no sugar inversion and no formation of the inhibitory compounds flavonoid, furfural, and 5-HMF. In the fermentation of the irradiated worts the dose of 20 kGy promoted the highest ethanol yield among the tested worts (0, 10, 20, and 40 kGy), showing the possibility of using electron beam for the treatment of wort, which allows decrease in losses caused by microbial contamination, in addition, allows increase in fermentation yield and productivity. In the AD and AC experiments, iron played an important role in decreasing the H2S production. In addition, the other metals made it possible to increase the methane yield. The vinasse AD and TE reactor (R2) reached a yield between 222.29-411.39 NmlCH4 g-1 VS, and the H2S in biogas remained below 500 ppm. The control reactor that did not received TE (R1) reached 36,000 ppm of H2S and failed due to acidification. However, after pH correction and TE addition, it was possible to re-establish AD in R1. In the AC reactors R3 and R4 after the addition of all TE, a yield between 54.61-109.14 NmlCH4 g-1 VS was observed in R3, and between 54.15-110.21 NmlCH4 g-1 VS in R4. Moreover, the H2S concentration remained below 186.42 ppm in R3 and below 70.74 in R4. In general, anaerobic co-digestion with the addition of metals maintained greater stability over the 238 days of experiment, with low accumulation of volatile fatty acids and H2S.